Optimalisasi Promosi Digital dalam Meningkatkan Minat Belajar Menjahit Pada LPK Anugrah Pratama - Intan Maharani; Dede Rahma Monica; Risky Achmad Hidayat; Nazwa Adhani Mahbub; Ridho Mohammad Jihad Aprilian; Yus Darusman (Jurnal Pendidikan dan Pengabdian Masyarakat, 2026)
The public's interest in sewing training at LPK Anugrah Pratama is still relatively low. This condition is influenced by the lack of optimal use of digital promotion as a medium for disseminating information about training programs. Although the institution already has several social media accounts such as Instagram, TikTok, Facebook, and WhatsApp, its use has not been carried out consistently so that the reach of information to the public is still limited. This service activity aims to increase people's interest in learning sewing skills through optimizing social media-based digital promotions at LPK Anugrah Pratama. The method of implementing activities includes the preparation, implementation, evaluation, and follow-up stages. The preparation stage is carried out through observation of the condition of social media and the level of interest in learning of participants. At the implementation stage, the creation and publication of digital content is carried out in stages in the form of videos of the sewing process, participants' work, and a learning atmosphere through the TikTok platform. The results of the activity show that the optimization of digital promotion has a positive influence on increasing people's interest in learning. More active social media activities are able to increase the dissemination of information about the training program so that the public becomes more familiar with LPK Anugrah Pratama. This can be seen from the increase in interaction on social media in the form of comments, personal messages, and questions related to training registration. In addition, there are people who express interest in participating in the training after seeing the uploaded content. Thus, digital promotion that is carried out consistently can be an effective strategy in increasing people's interest in sewing training.